Performance evaluation of the NG-TEST CARBA 5 and Genobio K.N.I.V.O. detection K-Set lateral flow assays for the detection of carbapenemases - Chloe N. Calica; Neda Domjacic; Jennifer Dacanay; Ethel C. de Carvalho Lopes; Mariel S. Mardoquio; Yan Chen; Ramzi Fattouh (Microbiology Spectrum)
ABSTRACT Infection with carbapenemase-producing organisms (CPOs) is associated with significant morbidity and mortality among hospitalized patients. Thus, the identification of CPOs is an important function of clinical microbiology laboratories. This study evaluates the performance of two lateral flow assays (LFAs), the NG-Test CARBA 5 (CARBA 5) and Genobio K.N.I.V.O. Detection K-Set (Genobio), for the detection of carbapenemases using well-characterized clinical and reference isolates of gram-negative bacterial species. Both LFAs are designed to detect KPC, NDM, VIM, IMP, and OXA-48-like carbapenemases from bacterial growth within 15 minutes. In total, 152 isolates were tested: 10 Acinetobacter baumannii, 12 Pseudomonas aeruginosa, and 130 from various Enterobacterales. Among these, 132 harbored a carbapenemase, and 20 were carbapenemase-negative. Additionally, LFAs were scored for background color and test indicator line intensity. For Enterobacterales, the CARBA 5 had an overall positive agreement of 100%, while Genobio had a positive agreement of 98.5% because of a failure to detect IMP in a Klebsiella pneumoniae isolate and false cross-reactivity for NDM and OXA-48 in a KPC-positive Morganella morganii. Both LFAs demonstrated a positive agreement of 100% among carbapenemase-producing A. baumannii and P. aeruginosa isolates. Neither LFA falsely detected carbapenemases among carbapenemase-negative isolates, nor was any positivity observed among isolates that carried an off-target carbapenemase. In terms of test indicator line intensity, both LFAs showed comparable performance; however, the Genobio LFA displayed a propensity for higher background signal. Overall, both LFAs demonstrated very good performance in detecting select carbapenemases and offered a fast turnaround time, straightforward interpretation, and minimal hands-on time.IMPORTANCEThis study contributes to the field by providing additional information on the performance of two commercial tests, known generally as lateral flow assays (LFA). These assays are used to identify a family of proteins, called carbapenemases, that cause antibiotic resistance and greatly limit the choices of antibiotics that can be used to treat infection. Our study evaluates the performance of two LFAs in a variety of bacteria, including some that are commonly studied (members of the Enterobacterales) as well as others where less test performance information is available (Pseudomonas aeruginosa and Acinetobacter baumannii). Our findings show that the LFAs provide a fast turnaround time and require minimal hands-on time in comparison to other tests. In addition, we provide information about practical factors that could negatively affect how the results are interpreted in busy clinical laboratories, such as the ease of “seeing” and interpreting the results.